2011
DOI: 10.1016/j.ajpath.2011.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 19 Epithelial Patterns in Cirrhotic Stroma Parallel Hepatocarcinogenesis

Abstract: Cirrhotic septa harbor vessels and inflammatory, fibrogenic, and ductular epithelial cells, collectively referred to as the ductular reaction (DR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Consistent with our findings, Cai et al [ 21 ] have found that proliferative ductular reaction is related to HPC activation in patients with combined hepatocellular-cholangiocarcinoma. Lennerz and colleagues [ 22 ] suggested marked alterations in cellular identity as an underlying mechanism for the reproducible perinodular DR that parallels progressive stages of intranodular hepatocarcinogenesis. Several studies have also shown that high levels of proliferation rate within DRs has been demonstrated in both oval cell-mediated liver regeneration in an animal model and human liver disease [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Cai et al [ 21 ] have found that proliferative ductular reaction is related to HPC activation in patients with combined hepatocellular-cholangiocarcinoma. Lennerz and colleagues [ 22 ] suggested marked alterations in cellular identity as an underlying mechanism for the reproducible perinodular DR that parallels progressive stages of intranodular hepatocarcinogenesis. Several studies have also shown that high levels of proliferation rate within DRs has been demonstrated in both oval cell-mediated liver regeneration in an animal model and human liver disease [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increased risk of hepatocarcinogenesis in HCV-infected patients whose biopsies showed foci of IHBCs may have common mechanisms with our proposed progenitor dominant regeneration with highest recurrence risk. 36 Alternatively, Lennerz et al 41 found a vanishing of DR with stepwise hepatocarcinogenesis in cirrhotic liver that may suggest the involvement of DR in HCC development, a novel hypothetical mechanism that DR may contribute to the generation of cancer-associated fibroblasts cross-talking with the microenvironment. These studies and our findings cumulatively suggest HPC activation may contribute to liver cancer recurrence by driving ''field cancerization.''…”
Section: Discussionmentioning
confidence: 99%
“…Markers of stemness have been associated with increased telomere length and chromosomal instability [11], microvascular invasion [12], high metastatic potential [13] and poor survival [14][15][16]. There is also increasing evidence suggesting that K19 immunohistochemical expression may be used as a prognostic marker in human HCC [10,14,[17][18][19][20][21][22]. However, the majority of these studies are based on HCC of Asian origin.…”
Section: Introductionmentioning
confidence: 99%